Research in the Department of Psychology: Notes on the path traversed - Vizcaíno G, Milcíades (Pensando Psicología, 2019)
Introduction: The modern university is characterized by having integrated research into its functions of teaching and institutional projection. Research is generally associated with the activity of the Faculties developing their academic and scientific objectives. The Cooperative University of Colombia has adopted this standard form and, in its academic programs, there are professionals who fulfill the role of both teacher and researcher. The Faculty of Psychology, since its inception in Villavicencio, has developed research projects. Objective: To look into the experience of the Prometeo research group to project the future of research, in accordance with the policies of the university and the requirements of COLCIENCIAS and the Ministry of National Education. An overview of the historical route with its predominant phases is presented, along with its trends, its products and ongoing projects. Methodology: A historical reconstruction was carried out based on the direct experience of members of Prometheus and reports submitted to the university and to COLCIENCIAS.